MS2 device: smartphone-facilitated mobile nucleic acid analysis on microfluidic device. Issue 12 (14th April 2021) - Wu, Xiaosong; Pan, Jingyu; Zhu, Xinchao; Hong, Chenggang; Hu, Anzhong; Zhu, Cancan; Liu, Yong; Yang, Ke; Zhu, Ling
Abstract : A mobile and universal nucleic acid analysis system integrated a microfluidic device and a smartphone. Abstract : Mobile sensing based on the integration of microfluidic devices and smartphones, so-called MS 2 technology, has enabled many applications over recent years and continues to stimulate growing interest in both research communities and industries. In particular, MS 2 technology has been proven to be able to be applied to molecular diagnostic analysis and can be implemented for basic research and clinical testing. However, the currently reported MS 2 -based nucleic acid analysis system has limited use in practical applications, because it is not integrated with quantitative PCR, multiplex PCR, and isothermal amplification functions, and lacks temperature control, image acquisition and real-time processing units with excellent performance. To provide a more universal and powerful platform, we here developed a novel MS 2 device by integrating a thermocycler, a multi fluorescence detection unit, a PCR chip, an isothermal chip, and a smartphone. The MS 2 device was approximately 325 mm ( L ) × 200 mm ( W ) × 200 mm ( H ) in volume and only 5 kg in weight, and showed an average power consumption of about 38.4 W. The entire nucleic acid amplification and analysis could be controlled through a self-made smartphone App. The maximum heating and cooling rates were 5 °C s −1 and 4 °C s −1, respectively. The entire PCR could be completed within 65 min. The temperature uniformity was less than 0.1 °C. Besides, the temperature stability over time (30 min) was within ±0.04 °C. Four optical channels were integrated (FAM, HEX, TAMRA, and ROX) on the MS 2 device. In particular, the PCR-based detection sensitivity reached 1 copy per μL, and the amplification efficiency was calculated to be 106.8%. Besides, the MS 2 device also was compatible with multiplex PCR and isothermal amplification. In short, the MS 2 device showed performance consistent with that of traditional commercial equipment. Thus, the MS 2 device provides an easy and integrated experimental platform for molecular diagnostic-related research and potential medical diagnostic applications.